Pengaruh Kegiatan Pembiasaan Literasi Dasar Terhadap Minat Baca Buku Fiksi Siswa Kelas VII SMP Negeri 137 Jakarta - Yunia Indah Lestari; Desy Safitri; Nandi Kurniawan (Departement of Mathematics Education, 2023)
This research is a quantitative study that aims to determine whether there is an effect of basic literacy habituation activities on interest in reading fiction books for class VII students at Junior High School 137 State of Jakarta. The population in this study were 214 students and a sample of 140 students, who were taken using simple random sampling technique. The variables used in this study are Basic Literacy Habituation Activities (X) and Interest in Reading Fiction Books (Y). The t test produced a sig value of 0.000 <0.05 and tcount 10.117 > ttable 1.977, which means that there is a significant influence between basic literacy habituation activities on students' interest in reading fiction books. The results of the correlation test obtained the value of the correlation coefficient r = 0.653, and it is known that the effect value of the basic literacy habituation activity variable on students' interest in reading fiction books is 42.6%.